Hand-drawn graph sketch matching for e-learning mathematics - Phan, Anh Tuan (2018)
Modern life becomes easier and more convenient for people around the world with the massive contribution of Internet technology to communicate and share information. Education has benefited from web technology with the rise of many e-learning systems. Many people prefer e-learning method due to its accessibility for everyone from everywhere on every moment. Because of its popularity, many e-learning systems are built to target different people on different subjects and with different mechanics to get high efficiency for learning online. The project focuses on developing Graph Sketching and Drawing questions of a web-based mathematics learning system. The main objective is to develop a mathematical graph editor and various techniques to match a sketched graph drawn by users with a stored graph as an ideal solution for the question. Also, those components need to be integrated as a part of the web learning system. During the project, the performance was evaluated based on testing samples from the current system’s data with some defined benchmark by the authors. Finally, some future improvements are suggested. The main focus of the system is to find a more effective graph editor with more customized features or to develop an editor, which is supported by current web technology. Other than that, different techniques can be exploited for matching images, which can be used for more complex graph sketching problems.